Cryogenic thermoelectric generation using cold energy from a decoupled liquid air energy storage system for decentralised energy networks. (1st January 2022) - Zhang, Tongtong; She, Xiaohui; You, Zhanping; Zhao, Yanqi; Fan, Hongjun; Ding, Yulong
Highlights: Liquid air is used to store, transport and release renewables (decoupled LAES). Thermoelectric generator is used to recover cryogenic energy from liquid air (Cryo-TEG). The LCOE of Cryo-TEG (0.0218 /kWh) is 4 times cheaper than traditional cycles. The Cryo-TEG is most favorable for the small-scale decoupled LAES (<6.4 MW). The decoupled LAES shows a round trip efficiency of 29% and a CCP efficiency of 50%. Abstract: Liquid Air Energy Storage (LAES) uses off-peak and/or renewable electricity to produce liquid air (charging). When needed, the liquid air expands in an expander to generate electricity (discharging). The produced liquid air can be transported from renewable energy rich areas to end-use sites using existing road, rail and shipping infrastructures. The discharging process occurs at the end-use sites in this case and is therefore decoupled from the charging process (denoted as decoupled LAES). One of key challenges associated with the decoupled LAES is the recovery of cryogenic energy released by liquid air during the discharging process. Here we propose a cryogenic thermoelectric generation (Cryo-TEG) method to effectively recover the cryogenic energy. Both thermodynamic and economic analyses are carried out on the Cryo-TEG. The results are compared with conventional cryogenic Rankine cycles (Cryo-RC). Additionally, system performance of the decoupled LAES integrated with the Cryo-TEG is also evaluated for combined power and cooling supply. The results show that the Cryo-TEG has a thermal efficiency of ∼ 9%, which is much lower than the Cryo-RC (∼39.5%). However, the Cryo-TEG gives a much better economic performance especially as the cooling capacity of liquid nitrogen is below 8.6 MW: the levelized cost of electricity of the Cryo-TEG could be as low as 0.0218 /kWh, ∼4 times cheaper than that of the Cryo-RC. This demonstrates that the Cryo-TEG is more favourable for cryogenic energy recovery in the small-scale decoupled LAES. With the Cryo-TEG, the decoupled LAES system could achieve an electrical round trip efficiency of ∼ 29% and a combined cooling and power efficiency of ∼ 50%.